Preparation process of light alloy conductor for new energy automobile

By dispersing modified graphene in aluminum alloy conductors using powder metallurgy, combined with multi-stage wire drawing processing and intermediate annealing process, the problem of low thermal conductivity and toughness of aluminum alloy conductors is solved, and high performance and low cost production of light alloy conductors for new energy vehicles is achieved.

CN119601298APending Publication Date: 2025-03-11ANHUI XINHAI GAODAO NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411626993.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The thermal conductivity and toughness of existing aluminum alloy conductors are relatively low, and cannot meet the requirements for light alloy conductors for new energy vehicles.

Method used

The surface-modified graphene is evenly dispersed inside the matrix aluminum alloy by powder metallurgy, and a multi-stage brushing and intermediate annealing process are used, combined with the appropriate amount of Sr, Sc, and Ce to improve the conductivity and strength.

Benefits of technology

It has achieved excellent conductivity, good strength and bending resistance of light alloy conductors for new energy vehicles, reduced production costs, and is suitable for industrial mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005134993330000081
    Figure BDA0005134993330000081
  • Figure BDA0005134993330000091
    Figure BDA0005134993330000091
  • Figure BDA0005134993330000101
    Figure BDA0005134993330000101
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum alloy conductor preparation, in particular to a preparation process of a light alloy conductor for a new energy automobile. The preparation process of the light alloy conductor for the new energy automobile comprises the following steps: firstly, preparing matrix aluminum alloy microspheres and graphene modified aluminum alloy microspheres; the matrix aluminum alloy microspheres and the graphene modified aluminum alloy microspheres are placed in a double-helix conical mixer according to the mass ratio of (11-16): 1 to be evenly mixed to obtain mixed alloy powder, and the mixed alloy powder is placed in a forming mold to be subjected to hot isostatic pressing treatment; and after cooling to room temperature, carrying out solution treatment, artificial aging treatment, first-stage wire drawing processing, first-stage intermediate annealing, second-stage wire drawing processing, second-stage intermediate annealing, third-stage wire drawing processing, third-stage intermediate annealing, fourth-stage wire drawing processing, fourth-stage intermediate annealing and final annealing treatment to obtain the finished light alloy conductor. The high-strength flexible cable has excellent electric conductivity and also has relatively good strength and deflection resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloy conductor preparation, and in particular to a process for preparing a light alloy conductor for new energy vehicles. Background Art

[0002] New energy vehicles can solve the carbon emission problem caused by the exhaust emissions of traditional fuel vehicles and have become the key development target of the domestic new energy industry. With the rapid development of new energy vehicles and the decline of policy subsidies, the cost of new energy vehicle companies is one of the reference standards for measuring corporate competitiveness. Wires, as the main power artery of new energy vehicles, account for a large part of the cost of new energy vehicles and are also one of the development directions for optimizing the quality of new energy vehicles.

[0003] Although traditional soft copper wires have good electrical conductivity, they are expensive and dense, which is not conducive to the cost optimization and lightweight design of new energy vehicles. Therefore, lighter aluminum or aluminum alloys are the key research direction for light alloy conductors for new energy vehicles.

[0004] The market background of aluminum or aluminum alloy as light alloy conductor is as follows: The density of aluminum is 2.7g / cm 3 , while the density of copper is 8.96g / cm 3 , that is, the specific gravity of aluminum is about 1 / 3 of that of copper, which has a good advantage of lightweight. The conductivity of pure copper is 1.7241×10 -8 Ω / m, the conductivity is 1.7241×10 -8 When Ω / m is taken as 100% IACS, the conductivity of aluminum is about 2 / 3 of that of copper, and the conductivity of aluminum is taken as 66% IACS. In order to ensure that the conductor can pass the same amount of current, the cross-sectional area of ​​the pure aluminum conductor is about 1.5 times that of the pure copper conductor. It can be seen that the ratio of aluminum or aluminum alloy as a light alloy conductor is only 1 / 2 of that of the pure copper conductor. With the current international copper price of about 70,000 yuan / ton and aluminum of about 18,800 yuan / ton, the weight is 3.7 times that of aluminum. With the rise in copper prices, "aluminum" replacing copper has become an inevitable choice for conductors of new energy vehicles.

[0005] The existing JIS-standard A1050, A1060, and A1070 aluminum alloy conductors have poor tensile durability, impact resistance, and bending properties, and cannot meet the use requirements of light alloy conductors for new energy vehicles. A high-conductivity aluminum alloy rod material disclosed in the invention patent with announcement number CN110629076B has an aluminum alloy material conductivity of 63.5-63.6% IACS, a tensile strength of 84-88 MPa, a yield strength of 52-60 MPa, and an elongation of 42-45%. It improves the strength of the aluminum alloy by adding a small amount of Fe, Ti, B, Mn, Si, Zn, Mg, La, and Ga, but inevitably reduces the overall conductivity of the aluminum alloy. To this end, the inventor provides a preparation process for a high-conductivity and tough light alloy conductor for new energy vehicles. Summary of the invention

[0006] In order to solve the problem of low thermal conductivity and toughness of aluminum alloy conductors in the prior art, the present invention provides a process for preparing light alloy conductors for new energy vehicles.

[0007] The present invention provides a light alloy conductor preparation process for new energy vehicles, which is achieved through the following technical solutions:

[0008] A process for preparing a light alloy conductor for new energy vehicles comprises the following steps:

[0009] Step 1, preparation of matrix aluminum alloy microspheres: according to the mass percentage of the elements of the matrix aluminum alloy microspheres, the mass percentage of the elements of the matrix aluminum alloy microspheres are as follows: 0.15% to 0.25% Mg, 0.15% to 0.25% Fe, 0.15% to 0.30% Cu, 0.10% to 0.20% Si, 0.003% to 0.005% Ti, 0.003% to 0.005% V, 0.05% to 0.15% Zr, 0.003% to 0.01% B, 0.002% ~0.01% Sr, 0.001%~0.01% Sc, 0.001%~0.01% Ce, the total content of inevitable impurities <0.15%, and the balance is aluminum; electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, and aluminum cerium alloys are placed in a smelting furnace at 690°C~710°C, and after all raw materials are completely melted, they are refined, degassed, and deslaged to obtain aluminum alloy melts, and then matrix aluminum alloy microspheres are obtained by a spray method;

[0010] Preparation of graphene-modified aluminum alloy microspheres: According to the element mass percentage of the graphene-modified aluminum alloy microspheres, the mass percentage of the elements of the graphene-modified aluminum alloy microspheres are as follows: 3-6% modified graphene, 0.15%-0.25% Mg, 0.15%-0.25% Fe, 0.15%-0.30% Cu, 0.10%-0.20% Si, 0.003%-0.005% Ti, 0.003%-0.005% V, 0.05%-0.15% Zr, 0.003%-0.01% B: 0.0 0.02% to 0.01% Sr: 0.001% to 0.01% Sc, 0.001% to 0.01% Ce, the total content of inevitable impurities <0.15%, and the balance is aluminum; placing electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene in a smelting furnace at 690° C. to 710° C., refining, degassing, and deslagging to obtain an aluminum alloy melt after all raw materials are completely melted, and then preparing graphene-modified aluminum alloy microspheres by a spray method;

[0011] The modified graphene is graphene modified with surface nano-aluminum clusters and / or graphene modified with single-atom aluminum;

[0012] Step 2, placing the matrix aluminum alloy microspheres and graphene-modified aluminum alloy microspheres prepared in step 1 in a double-helix conical mixer at a mass ratio of (11-16):1 and mixing them evenly to obtain a mixed alloy powder;

[0013] Step 3, placing the mixed alloy powder obtained in step 2 in a forming mold for hot isostatic pressing, cooling to room temperature, performing solution treatment and artificial aging treatment to obtain an aluminum alloy rod with a diameter of 8-12 mm;

[0014] Step 4: Aluminum alloy bars with a diameter of 8-12 mm are subjected to primary wire drawing and primary intermediate annealing. The diameter of the aluminum alloy bars with a diameter of 8-12 mm is marked as Φ 初 The angle α of the extrusion die used in the primary wire drawing process is 15-30°, the primary intermediate annealing parameters are 360-385℃ for 80-160min, and the diameter of the aluminum alloy rod obtained by the primary wire drawing process and the primary intermediate annealing is Φ1, Φ1=0.3-0.6Φ 初 ;

[0015] Step 5: The aluminum alloy bar with a diameter of Φ1 in step 4 is subjected to secondary wire drawing and secondary intermediate annealing. The angle α of the extrusion die used in the secondary wire drawing is 15-30°, and the secondary intermediate annealing parameters are 360-385°C for 80-160min. The diameter of the aluminum alloy bar obtained by the secondary wire drawing and the secondary intermediate annealing is Φ2, Φ2=0.15-0.30Φ初 ;

[0016] Step 6: The aluminum alloy bar with a diameter of Φ2 in step 5 is subjected to three-stage wire drawing and three-stage intermediate annealing. The angle α of the extrusion die used in the three-stage wire drawing is 15-30°, and the three-stage intermediate annealing parameters are 360-385°C for 80-160min. The diameter of the aluminum alloy bar obtained by the three-stage wire drawing and the three-stage intermediate annealing is Φ3, Φ3=0.08-0.15Φ 初 ;

[0017] Step 7: The aluminum alloy bar with a diameter of Φ3 in step 6 is subjected to four-stage wire drawing and four-stage intermediate annealing. The angle α of the extrusion die used in the four-stage wire drawing is 15-30°, and the four-stage intermediate annealing parameters are 360-385°C for 80-160min. The diameter of the aluminum alloy bar obtained by the four-stage wire drawing and four-stage intermediate annealing is Φ4, Φ4=0.03-0.06Φ 初 ;

[0018] Step eight, the aluminum alloy rod with a diameter of Φ4 in step seven is subjected to final annealing treatment to obtain a finished light alloy conductor, and the final annealing treatment parameters are as follows: continuous heat treatment at 480-540° C. for 0.40-0.50 s.

[0019] In the present invention, the surface-modified graphene is evenly dispersed in the matrix aluminum alloy by powder metallurgy, and the grain refinement effect can be effectively improved by adding appropriate amounts of Sr, Sc and Ce into the matrix aluminum alloy. The corresponding multi-stage wire drawing + multi-stage intermediate annealing + final annealing process is combined to effectively avoid the wire drawing breakage problem caused by the addition of the surface-modified graphene. The finally prepared light alloy conductor for new energy vehicles has excellent electrical conductivity and good strength and flexural resistance.

[0020] Preferably, in the step 2, the base aluminum alloy microspheres and graphene-modified aluminum alloy microspheres prepared in the step 1 are placed in a double-helix conical mixer at a mass ratio of (11-16):1, and after introducing argon gas to replace the air, the temperature of the introduced argon gas is 0-5°C, and under the protection of argon gas, the mixture is mixed at a speed of 600-800 rpm for 2-4 hours to obtain a mixed alloy powder.

[0021] Preferably, the hot isostatic pressing treatment parameters in step 3 are as follows: molding temperature 480-580°C, molding pressure: first pressurize to 200±20MPa at 20MPa / s, hold pressure for 30±5s, then pressurize to 300±20MPa at 10MPa / s, hold pressure for 30±5s, then pressurize to 400±20MPa at 5MPa / s, hold pressure for 30±5s, then pressurize to 460±20MPa at 1MPa / s, hold pressure for 60±5s, then pressurize to 560±20MPa at 0.5MPa / s, hold pressure for 100±5s, then reduce pressure to 300±20MPa at 1.0MPa / s, hold pressure for 60±5s, then reduce pressure to 200±20MPa at 5MPa / s MPa, hold the pressure for 60±5s, then reduce the pressure at 10MPa / s to 100±20MPaMPa, hold the pressure for 60±5s, and finally reduce the pressure at 20MPa / s to 0MPa. The forming speed is 0.2-2mm / s. After cooling to room temperature, the burrs are polished to obtain the semi-finished aluminum alloy bar.

[0022] Preferably, the solution treatment parameters in step three are as follows: quenching at 540-560° C. for 1-4 hours.

[0023] Preferably, the artificial aging treatment parameters in step 3 are as follows: keeping warm at 150-180° C. for 0.1-4 h.

[0024] By optimizing the process parameters of powder metallurgy, it helps to refine the grains and improve the tensile strength, bending fatigue resistance and heat resistance of semi-finished aluminum alloy bars, which helps to improve the quality of aluminum alloy wires.

[0025] Preferably, the first-stage intermediate annealing parameter of step 4 is 360°C for 100-120 min, and the diameter of the aluminum alloy bar obtained by the first-stage wire drawing and the first-stage intermediate annealing is Φ1, Φ1=0.40Φ 初 .

[0026] Preferably, the secondary intermediate annealing parameters of step 5 are 370°C for 100-120 min, and the diameter of the aluminum alloy rod obtained by secondary wire drawing and secondary intermediate annealing is Φ2, Φ2=0.20Φ 初 .

[0027] Preferably, the three-stage intermediate annealing parameters of step 6 are 380°C for 100-120 min, and the diameter of the aluminum alloy rod obtained by the three-stage wire drawing and the three-stage intermediate annealing is Φ3, Φ3=0.10Φ 初 .

[0028] Preferably, the parameters of the four-stage intermediate annealing in step seven are 385°C for 100-120 min, and the diameter of the aluminum alloy rod obtained by the four-stage wire drawing and the four-stage intermediate annealing is Φ4, Φ4=0.03-0.06Φ初 The diameter of the aluminum alloy bar Φ4 is customized according to actual needs.

[0029] By optimizing the process parameters of wire drawing + intermediate annealing, the thinnest aluminum alloy wire can be 0.5mm, which gives the light aluminum alloy wire excellent processing performance and facilitates the subsequent preparation of multi-strand aluminum alloy twisted wire.

[0030] Preferably, the surface nano-aluminum cluster loading rate in the graphene modified with surface nano-aluminum clusters is 8-20wt%; the single-atom aluminum loading rate in the single-atom aluminum modified graphene is 5-10wt%.

[0031] By adopting the above technical solution, the dispersion uniformity of graphene can be improved, thereby ensuring that the finally prepared light aluminum alloy wire has good conductivity while also having good strength and flexural resistance.

[0032] In summary, the present invention has the following advantages:

[0033] 1. The present invention has excellent electrical conductivity and good strength and flexural resistance.

[0034] 2. The preparation method of the present invention has relatively low operational difficulty and is suitable for industrial batch production.

[0035] 3. The preparation method of the present invention can produce a 0.5 mm aluminum alloy wire with excellent processability.

[0036] 4. The light aluminum alloy wire prepared in the present invention has a conductivity of more than 68% IACS, a tensile strength of more than 100 MPa, a yield strength of 60 MPa, and an elongation of more than 10%. DETAILED DESCRIPTION

[0037] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples.

[0038] Example

[0039] A process for preparing a light alloy conductor for new energy vehicles comprises the following steps:

[0040] Step 1, preparation of matrix aluminum alloy microspheres: According to the mass percentage of the elements of the matrix aluminum alloy microspheres, the mass percentage of the elements of the matrix aluminum alloy microspheres are as follows: 0.15% to 0.25% Mg, 0.15% to 0.25% Fe, 0.15% to 0.30% Cu, 0.10% to 0.20% Si, 0.003% to 0.005% Ti, 0.003% to 0.005% V, 0.05% to 0.15% Zr, 0.003% to 0.01% B, 0.002% to 0.01% Sr, 0.001% to 0.01% Sc, 0.001% to 0.01% Ce, the total content of inevitable impurities <0.15%, and the balance is aluminum; electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, and aluminum cerium alloys are placed in a smelting furnace at 690° C. to 710° C., and after all raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then matrix aluminum alloy microspheres are obtained by a spray method;

[0041] Preparation of graphene-modified aluminum alloy microspheres: According to the element mass percentage of the graphene-modified aluminum alloy microspheres, the mass percentage of the elements of the graphene-modified aluminum alloy microspheres are as follows: 3-6% modified graphene, 0.15%-0.25% Mg, 0.15%-0.25% Fe, 0.15%-0.30% Cu, 0.10%-0.20% Si, 0.003%-0.005% Ti, 0.003%-0.005% V, 0.05%-0.15% Zr, 0.003%-0.01% B: 0.00 2% to 0.01% Sr: 0.001% to 0.01% Sc, 0.001% to 0.01% Ce, the total content of inevitable impurities <0.15%, and the balance is aluminum; electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene are placed in a smelting furnace at 690° C. to 710° C., and after all raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres are obtained by a spray method;

[0042] The modified graphene is graphene modified with surface nano-aluminum clusters and / or graphene modified with single-atom aluminum;

[0043] The surface nano-aluminum cluster loading rate in the graphene modified with the surface nano-aluminum clusters is 8-20wt%;

[0044] The loading rate of single-atom aluminum in single-atom aluminum-modified graphene is 5-10wt%;

[0045] Step 2, placing the matrix aluminum alloy microspheres and graphene-modified aluminum alloy microspheres prepared in step 1 in a double-helix conical mixer at a mass ratio of (11-16):1 and mixing them evenly to obtain a mixed alloy powder;

[0046] Preferably, in step 2, the base aluminum alloy microspheres and the graphene-modified aluminum alloy microspheres prepared in step 1 are placed in a double-helix conical mixer at a mass ratio of (11-16):1, and after introducing argon gas to replace the air, the temperature of the introduced argon gas is 0-5°C, and under the protection of argon gas, the mixture is mixed at a speed of 600-800 rpm for 2-4 hours to obtain a mixed alloy powder;

[0047] Step 3, placing the mixed alloy powder obtained in step 2 in a forming mold for hot isostatic pressing, cooling to room temperature, performing solution treatment and artificial aging treatment to obtain an aluminum alloy rod with a diameter of 8-12 mm;

[0048] The hot isostatic pressing treatment parameters in step 3 are as follows: molding temperature 480-580°C, molding pressure: first pressurize to 200±20MPa at 20MPa / s, hold pressure for 30±5s, then pressurize to 300±20MPa at 10MPa / s, hold pressure for 30±5s, then pressurize to 400±20MPa at 5MPa / s, hold pressure for 30±5s, then pressurize to 460±20MPa at 1MPa / s, hold pressure for 60±5s, then pressurize to 560±20MPa at 0.5MPa / s, hold pressure for 100±5s, then reduce pressure to 300±20MPa at 1.0MPa / s, hold pressure for 60±5s, then reduce pressure to 200±20MPa at 5MPa / s, hold pressure for 60±5s, then reduce pressure to 100±20MPa at 10MPa / s. MPa, maintain the pressure for 60±5s, and finally reduce the pressure to 0MPa at 20MPa / s, the forming speed is 0.2-2mm / s, cool to room temperature, and grind the burrs to obtain the semi-finished aluminum alloy bar;

[0049] The solution treatment parameters in step 3 are as follows: quenching at 540-560°C for 1-4h;

[0050] The artificial aging treatment parameters in step 3 are as follows: 150-180°C for 0.1-4h;

[0051] Step 4: Aluminum alloy bars with a diameter of 8-12 mm are subjected to primary wire drawing and primary intermediate annealing. The diameter of the aluminum alloy bars with a diameter of 8-12 mm is marked as Φ 初 The angle α of the extrusion die used in the primary wire drawing process is 15-30°, the primary intermediate annealing parameters are 360-385℃ for 80-160min, and the diameter of the aluminum alloy rod obtained by the primary wire drawing process and the primary intermediate annealing is Φ1, Φ1=0.3-0.6Φ 初 ;

[0052] Preferably, the first-stage intermediate annealing parameter of step 4 is 360°C for 100-120 min, and the diameter of the aluminum alloy rod obtained by the first-stage wire drawing and the first-stage intermediate annealing is Φ1, Φ1=0.40Φ 初

[0053] Step 5: The aluminum alloy bar with a diameter of Φ1 in step 4 is subjected to secondary wire drawing and secondary intermediate annealing. The angle α of the extrusion die used in the secondary wire drawing is 15-30°, and the secondary intermediate annealing parameters are 360-385°C for 80-160min. The diameter of the aluminum alloy bar obtained by the secondary wire drawing and the secondary intermediate annealing is Φ2, Φ2=0.15-0.30Φ 初 ;

[0054] Preferably, the secondary intermediate annealing parameters of step 5 are 370°C for 100-120 min, and the diameter of the aluminum alloy rod obtained by secondary wire drawing and secondary intermediate annealing is Φ2, Φ2=0.20Φ 初

[0055] Step 6: The aluminum alloy bar with a diameter of Φ2 in step 5 is subjected to three-stage wire drawing and three-stage intermediate annealing. The angle α of the extrusion die used in the three-stage wire drawing is 15-30°, and the three-stage intermediate annealing parameters are 360-385°C for 80-160min. The diameter of the aluminum alloy bar obtained by the three-stage wire drawing and the three-stage intermediate annealing is Φ3, Φ3=0.08-0.15Φ 初 ;

[0056] Preferably, the three-stage intermediate annealing parameters of step 6 are 380°C for 100-120 min, and the diameter of the aluminum alloy rod obtained by the three-stage wire drawing and the three-stage intermediate annealing is Φ3, Φ3 = 0.10Φ 初

[0057] Step 7: The aluminum alloy bar with a diameter of Φ3 in step 6 is subjected to four-stage wire drawing and four-stage intermediate annealing. The angle α of the extrusion die used in the four-stage wire drawing is 15-30°, and the four-stage intermediate annealing parameters are 360-385°C for 80-160min. The diameter of the aluminum alloy bar obtained by the four-stage wire drawing and four-stage intermediate annealing is Φ4, Φ4=0.03-0.06Φ 初 ;

[0058] Preferably, the parameters of the four-stage intermediate annealing in step seven are 385°C for 100-120 min, and the diameter of the aluminum alloy rod obtained by the four-stage wire drawing and the four-stage intermediate annealing is Φ4, Φ4 = 0.03-0.06Φ 初 The diameter of the aluminum alloy bar is Φ4, which is customized according to actual needs.

[0059] Step eight, the aluminum alloy rod with a diameter of Φ4 in step seven is subjected to final annealing treatment to obtain a finished light alloy conductor, and the final annealing treatment parameters are as follows: continuous heat treatment at 480-540° C. for 0.40-0.50 s.

[0060] Preparation Example

[0061] The element mass percentage ingredients of the matrix aluminum alloy microspheres in Preparation Examples 1-7 are shown in Table 1.

[0062] Table 1: Element mass percentage ingredients of the matrix aluminum alloy microspheres of Preparation Examples 1-7

[0063]

[0064] The element mass percentage ingredients of the graphene-modified aluminum alloy microspheres in Preparation Examples 8-15 are shown in Table 2.

[0065] Table 2: Element mass percentage ingredients of graphene modified aluminum alloy microspheres of Preparation Examples 8-15

[0066]

[0067]

[0068] The element mass percentage composition table of the matrix aluminum alloy microspheres in comparative preparation examples 1-6 is shown in Table 3.

[0069] Table 3: Element mass percentage ingredients of the matrix aluminum alloy microspheres in comparative preparation examples 1-6

[0070]

[0071]

[0072] The element mass percentage ingredient list of the graphene-modified aluminum alloy microspheres in comparative preparation examples 7-15 is shown in Table 4.

[0073] Table 4: Element mass percentage ingredients of graphene modified aluminum alloy microspheres in comparative preparation examples 7-15

[0074]

[0075]

[0076] The element mass percentage ingredients of the graphene modified aluminum alloy microspheres in comparative preparation examples 1-6 are shown in Table 5.

[0077] Table 5: Element mass percentage ingredients of graphene modified aluminum alloy microspheres in comparative preparation examples 1-6

[0078]

[0079]

[0080] The element mass percentage ingredients of the graphene modified aluminum alloy microspheres in comparative preparation examples 1-6 are shown in Table 6.

[0081] Table 6: Element mass percentage ingredients of graphene modified aluminum alloy microspheres in comparative preparation examples 1-6

[0082]

[0083]

[0084] The graphene-modified aluminum alloy A is a graphene modified with nano-aluminum clusters prepared by a sol-gel method from Guangzhou Zhongshan Functional Materials Co., Ltd., and the loading rate of the nano-aluminum clusters is 8.84 wt%.

[0085] Graphene modified aluminum alloy B is derived from single-atom aluminum modified graphene customized by Beijing Graphene Technology Research Institute Co., Ltd., with a single-atom aluminum loading of 5.36 wt%.

[0086] The graphene-modified aluminum alloy C was obtained from graphene modified with nano-aluminum clusters prepared by a sol-gel method from Guangzhou Zhongshan Functional Materials Co., Ltd. The loading rate of the nano-aluminum clusters was 3.27 wt %.

[0087] Graphene modified aluminum alloy D is from single-atom aluminum modified graphene customized by Beijing Graphene Technology Research Institute Co., Ltd., with a single-atom aluminum loading of 2.15 wt%.

[0088] Embodiment 1: A process for preparing a light alloy conductor for new energy vehicles, comprising the following steps:

[0089] A process for preparing a light alloy conductor for new energy vehicles comprises the following steps:

[0090] Step 1, preparation of matrix aluminum alloy microspheres: according to the mass percentage of the elements of the matrix aluminum alloy microspheres in Preparation Example 1 in Table 1, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, and aluminum cerium alloys are placed in a smelting furnace at 700°C, and after all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then the matrix aluminum alloy microspheres are obtained by spraying, and the particle size D 50 =13.5 μm;

[0091] At the same time, graphene-modified aluminum alloy microspheres were prepared: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in Preparation Example 8 in Table 2, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene were placed in a smelting furnace at 700° C. After all the raw materials were completely melted, they were refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres with a particle size D were obtained by a spray method. 50 =13.8 μm;

[0092] Step 2: Place the matrix aluminum alloy microspheres and graphene-modified aluminum alloy microspheres prepared in step 1 in a double-helix conical mixer at a mass ratio of 11:1, introduce argon gas to replace the air, introduce argon gas at a temperature of 0°C, and mix at a speed of 800 rpm for 2 hours under argon protection to obtain a mixed alloy powder;

[0093] Step three, placing the mixed alloy powder obtained in step two in a molding mold for hot isostatic pressing treatment, and the hot isostatic pressing treatment parameters are as follows: molding temperature 560°C, molding pressure: first pressurize to 200MPa at 20MPa / s, hold pressure for 30s, then pressurize to 300MPa at 10MPa / s, hold pressure for 30s, then pressurize to 400MPa at 5MPa / s, hold pressure for 30s, then pressurize to 460MPa at 1MPa / s, hold pressure for 60s, then pressurize to 560MPa at 0.5MPa / s, hold pressure for 100s, then reduce the pressure to 3000MPa at 1.0MPa / s, hold pressure for 60s, then reduce the pressure to 200MPa MPa at 5MPa / s, hold pressure for 60s, and then reduce the pressure to 100MPa at 10MPa / s MPa, hold the pressure for 60s, and finally reduce the pressure to 0MPa at 20MPa / s, the forming speed is 0.5mm / s, cool to room temperature, grind the burrs to get the semi-finished aluminum alloy bar, cool to room temperature and perform solid solution treatment, the solid solution treatment parameters are as follows: keep at 560℃ for 2h, water quench to room temperature, and then perform artificial aging treatment, the artificial aging treatment parameters are as follows: keep at 165℃ for 0.5h, and you can get an aluminum alloy bar with a diameter of 10mm;

[0094] Step 4: The aluminum alloy bar with a diameter of 10 mm is subjected to primary wire drawing and primary intermediate annealing. The angle α of the extrusion die used in the primary wire drawing is 30°, and the primary intermediate annealing parameter is 360° C. for 120 min. After the primary wire drawing and the primary intermediate annealing, an aluminum alloy bar with a diameter of 4 mm is obtained;

[0095] Step 5, the aluminum alloy bar with a diameter of 4 mm in step 4 is subjected to secondary wire drawing and secondary intermediate annealing, the angle α of the extrusion die used in the secondary wire drawing is 30°, the secondary intermediate annealing parameter is 370°C and kept warm for 120 minutes, and the secondary wire drawing and secondary intermediate annealing are performed to obtain an aluminum alloy bar with a diameter of 2 mm;

[0096] Step 6, the aluminum alloy bar with a diameter of 2 mm in step 5 is subjected to three-stage wire drawing and three-stage intermediate annealing, the angle α of the extrusion die used in the three-stage wire drawing is 30°, and the three-stage intermediate annealing parameters are 380°C and 120min of heat preservation, and the three-stage wire drawing and three-stage intermediate annealing are performed to obtain an aluminum alloy bar with a diameter of 1 mm;

[0097] Step 7, the aluminum alloy bar with a diameter of 1 mm in step 6 is subjected to four-stage wire drawing and four-stage intermediate annealing, the angle α of the extrusion die used in the four-stage wire drawing is 30°, the four-stage intermediate annealing parameter is 385°C for 120 minutes, and the aluminum alloy bar with a diameter of 0.5 mm is obtained after the four-stage wire drawing and four-stage intermediate annealing;

[0098] Step eight, the aluminum alloy bar with a diameter of 0.5 mm in step seven is subjected to final annealing treatment: continuous heat treatment at 525° C. for 0.50 s to obtain a finished light alloy conductor for new energy vehicles.

[0099] The difference between Example 2 and Example 1 is that: Step 2, the base aluminum alloy microspheres and graphene modified aluminum alloy microspheres prepared in Step 1 are placed in a double-helix conical mixer at a mass ratio of 12:1, and argon gas is introduced to replace the air. The argon gas temperature is 0°C, and under the protection of argon gas, the mixture is mixed at a speed of 800 rpm for 2 hours to obtain a mixed alloy powder.

[0100] The difference between Example 3 and Example 1 is that: Step 2, the base aluminum alloy microspheres and graphene modified aluminum alloy microspheres prepared in Step 1 are placed in a double-helix conical mixer at a mass ratio of 13:1, and argon gas is introduced to replace the air. The argon gas temperature is 0°C, and under the protection of argon gas, mixing is carried out at a speed of 800 rpm for 2 hours to obtain a mixed alloy powder.

[0101] The difference between Example 4 and Example 1 is that: Step 2, the base aluminum alloy microspheres and graphene modified aluminum alloy microspheres prepared in Step 1 are placed in a double-helix conical mixer at a mass ratio of 14:1, and argon gas is introduced to replace the air. The argon gas temperature is 0°C, and under the protection of argon gas, the mixture is mixed at a speed of 800 rpm for 2 hours to obtain a mixed alloy powder.

[0102] The difference between Example 5 and Example 1 is that: Step 2, the base aluminum alloy microspheres and graphene modified aluminum alloy microspheres prepared in Step 1 are placed in a double-helix conical mixer at a mass ratio of 15:1, and argon gas is introduced to replace the air. The argon gas temperature is 0°C, and under the protection of argon gas, mixing is carried out at a speed of 800 rpm for 2 hours to obtain a mixed alloy powder.

[0103] The difference between Example 6 and Example 1 is that: Step 2, the base aluminum alloy microspheres and graphene modified aluminum alloy microspheres prepared in Step 1 are placed in a double-helix conical mixer at a mass ratio of 16:1, and argon gas is introduced to replace the air. The argon gas temperature is 0°C, and under the protection of argon gas, mixing is carried out at a speed of 800 rpm for 2 hours to obtain a mixed alloy powder.

[0104] The difference between Example 7 and Example 1 is that: Step 1, preparation of matrix aluminum alloy microspheres: according to the mass percentage of the elements of the matrix aluminum alloy microspheres in Preparation Example 2 in Table 1, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, and aluminum cerium alloys are placed in a smelting furnace at 700° C. After all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then matrix aluminum alloy microspheres are obtained by spraying, and the particle size D 50 =13.3 μm;

[0105] At the same time, the preparation of graphene-modified aluminum alloy microspheres was prepared: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in the comparative preparation example 1 in Table 5, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene were placed in a smelting furnace at 700° C. After all the raw materials were completely melted, they were refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres with a particle size D were obtained by a spray method. 50 =13.6 microns.

[0106] The difference between Example 8 and Example 1 is that: Step 1, preparation of matrix aluminum alloy microspheres: according to the mass percentage of the elements of the matrix aluminum alloy microspheres in Preparation Example 3 in Table 1, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, and aluminum cerium alloys are placed in a smelting furnace at 700° C. After all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then matrix aluminum alloy microspheres are obtained by spraying, and the particle size D 50 =13.5 μm;

[0107] At the same time, the preparation of graphene-modified aluminum alloy microspheres was prepared: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in the comparative preparation example 2 in Table 5, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene were placed in a smelting furnace at 700° C. After all the raw materials were completely melted, they were refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres with a particle size D were obtained by a spray method. 50 =13.8 microns.

[0108] The difference between Example 9 and Example 1 is that: Step 1, preparation of matrix aluminum alloy microspheres: according to the mass percentage of the elements of the matrix aluminum alloy microspheres in Preparation Example 4 in Table 1, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, and aluminum cerium alloys are placed in a smelting furnace at 700° C. After all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then matrix aluminum alloy microspheres are obtained by spraying, and the particle size D 50 =13.4 μm;

[0109] At the same time, the preparation of graphene-modified aluminum alloy microspheres was prepared: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in the comparative preparation example 3 in Table 5, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene were placed in a smelting furnace at 700° C. After all the raw materials were completely melted, they were refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres with a particle size D were obtained by a spray method. 50 =13.9 microns.

[0110] The difference between Example 10 and Example 1 is that: Step 1, preparation of matrix aluminum alloy microspheres: electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, and aluminum cerium alloys are placed in a smelting furnace at 700° C. after all raw materials are completely melted, and then refined, degassed, and deslaged to obtain an aluminum alloy melt, and then matrix aluminum alloy microspheres are obtained by spraying, and the particle size D 50 =13.1 μm;

[0111] At the same time, the preparation of graphene-modified aluminum alloy microspheres was prepared: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in the comparative preparation example 4 in Table 5, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene were placed in a smelting furnace at 700° C. After all the raw materials were completely melted, they were refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres with a particle size D were obtained by a spray method. 50 =13.5 microns.

[0112] The difference between Example 11 and Example 1 is that: Step 1, preparation of matrix aluminum alloy microspheres: according to the mass percentage of the elements of the matrix aluminum alloy microspheres in Preparation Example 6 in Table 1, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, and aluminum cerium alloys are placed in a smelting furnace at 700° C. After all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then matrix aluminum alloy microspheres with a particle size D are obtained by a spray method. 50 =13.4 μm;

[0113] At the same time, the preparation of graphene-modified aluminum alloy microspheres was prepared: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in the comparative preparation example 5 in Table 5, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene were placed in a smelting furnace at 700° C. After all the raw materials were completely melted, they were refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres with a particle size D were obtained by a spray method. 50 =13.9 microns.

[0114] The difference between Example 12 and Example 1 is that: Step 1, preparation of matrix aluminum alloy microspheres: according to the mass percentage of the elements of the matrix aluminum alloy microspheres in Preparation Example 7 in Table 1, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, and aluminum cerium alloys are placed in a smelting furnace at 700° C., and after all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then matrix aluminum alloy microspheres are obtained by spraying, and the particle size D 50 =13.5 μm;

[0115] At the same time, the preparation of graphene-modified aluminum alloy microspheres was prepared: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in the comparative preparation example 6 in Table 5, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene were placed in a smelting furnace at 700° C. After all the raw materials were completely melted, they were refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres with a particle size D were obtained by a spray method. 50 =13.8 microns.

[0116] The difference between Example 13 and Example 1 is that: in step 1, the preparation of graphene-modified aluminum alloy microspheres is as follows: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in Preparation Example 9 in Table 2, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene are placed in a smelting furnace at 700° C., and after all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres are obtained by a spray method, and the particle size D 50 =13.6 microns.

[0117] The difference between Example 14 and Example 1 is that: in step 1, the preparation of graphene-modified aluminum alloy microspheres is as follows: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in Preparation Example 10 in Table 2, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene are placed in a smelting furnace at 700° C., and after all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres are obtained by a spray method, and the particle size D 50 =13.2 microns.

[0118] The difference between Example 15 and Example 1 is that: in step 1, the preparation of graphene-modified aluminum alloy microspheres is as follows: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in Preparation Example 11 in Table 2, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene are placed in a smelting furnace at 700° C., and after all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres are obtained by a spray method, and the particle size D 50 =13.9 microns.

[0119] The difference between Example 16 and Example 1 is that: in step 1, the preparation of graphene-modified aluminum alloy microspheres is as follows: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in Preparation Example 12 in Table 2, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene are placed in a smelting furnace at 700° C., and after all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres are obtained by a spray method, and the particle size D 50 =13.6 microns.

[0120] The difference between Example 17 and Example 1 is that: in step 1, the preparation of graphene-modified aluminum alloy microspheres is as follows: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in Preparation Example 13 in Table 2, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene are placed in a smelting furnace at 700° C., and after all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres are obtained by a spray method, and the particle size D 50 =13.5 microns.

[0121] The difference between Example 18 and Example 1 is that: in step 1, the preparation of graphene-modified aluminum alloy microspheres is as follows: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in Preparation Example 14 in Table 2, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene are placed in a smelting furnace at 700° C., and after all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres are obtained by a spray method, and the particle size D 50 =13.7 microns.

[0122] The difference between Example 19 and Example 1 is that: in step 1, the preparation of graphene-modified aluminum alloy microspheres is as follows: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in Preparation Example 15 in Table 2, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene are placed in a smelting furnace at 700° C., and after all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres are obtained by a spray method, and the particle size D 50 =13.4 microns.

[0123] The difference between Example 20 and Example 1 is that: Step 3, the mixed alloy powder obtained in Step 2 is placed in a molding mold for hot isostatic pressing, and the hot isostatic pressing parameters are as follows: molding temperature 560°C, molding pressure: first pressurized to 200MPa at 20MPa / s, maintained for 30s, then pressurized to 400MPa at 5MPa / s, maintained for 120s, then pressurized to 560MPa at 1MPa / s, maintained for 240s, and then reduced to 100MPa at 10MPa / s MPa, hold the pressure for 180s, and finally reduce the pressure at 20MPa / s to 0MPa. The forming speed is 0.5mm / s, cool to room temperature, and grind the burrs to obtain the semi-finished aluminum alloy bar. After cooling to room temperature, solution treatment is carried out. The solution treatment parameters are as follows: keep warm at 560℃ for 2h, water quench to room temperature, and then carry out artificial aging treatment. The artificial aging treatment parameters are as follows: keep warm at 165℃ for 0.5h, and you can get an aluminum alloy bar with a diameter of 10mm.

[0124] The difference between Comparative Example 1 and Example 1 is that: Step 2, the base aluminum alloy microspheres prepared in Step 1 are placed in a double-helix conical mixer, argon gas is introduced to replace the air, the argon temperature is 0°C, and under argon protection, mixing is performed at 800 rpm for 2 hours to obtain a mixed alloy powder.

[0125] The difference between Comparative Example 2 and Example 1 is that: Step 2, the base aluminum alloy microspheres and graphene-modified aluminum alloy microspheres prepared in Step 1 are placed in a double-helix conical mixer at a mass ratio of 9:1, and argon gas is introduced to replace the air. The argon gas temperature is 0°C, and under the protection of argon gas, the mixture is mixed at a speed of 800 rpm for 2 hours to obtain a mixed alloy powder.

[0126] The difference between Comparative Example 3 and Example 1 is that: Step 2, the base aluminum alloy microspheres and graphene-modified aluminum alloy microspheres prepared in Step 1 are placed in a double-helix conical mixer at a mass ratio of 19:1, and argon gas is introduced to replace the air. The argon gas temperature is 0°C, and under the protection of argon gas, the mixture is mixed at a speed of 800 rpm for 2 hours to obtain a mixed alloy powder.

[0127] The difference between Comparative Example 4 and Example 1 is that: Step 1, preparation of matrix aluminum alloy microspheres: According to the mass percentage of the elements of the matrix aluminum alloy microspheres in Comparative Preparation Example 1 in Table 3, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, and aluminum cerium alloys are placed in a smelting furnace at 700° C. After all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then the matrix aluminum alloy microspheres are prepared by a spray method, and the particle size D 50 =13.5 μm;

[0128] At the same time, graphene-modified aluminum alloy microspheres are prepared: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in comparative example 1 in Table 6, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene are placed in a smelting furnace at 700° C. After all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres are obtained by a spray method, with a particle size D 50 =13.8 microns.

[0129] The difference between Comparative Example 5 and Example 1 is that: Step 1, preparation of matrix aluminum alloy microspheres: According to the mass percentage of the elements of the matrix aluminum alloy microspheres in Comparative Preparation Example 2 in Table 3, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, and aluminum cerium alloys are placed in a smelting furnace at 700° C. After all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then matrix aluminum alloy microspheres are obtained by spraying, and the particle size D 50 =13.5 μm;

[0130] At the same time, graphene-modified aluminum alloy microspheres were prepared: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in comparative example 2 in Table 6, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene were placed in a smelting furnace at 700° C. After all the raw materials were completely melted, they were refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres were obtained by a spray method, with a particle size D 50 =13.9 microns.

[0131] The difference between Comparative Example 6 and Example 1 is that: Step 1, preparation of matrix aluminum alloy microspheres: According to the mass percentage of the elements of the matrix aluminum alloy microspheres in Comparative Preparation Example 3 in Table 3, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, and aluminum cerium alloys are placed in a smelting furnace at 700° C. After all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then the matrix aluminum alloy microspheres are prepared by a spray method, and the particle size D 50 =13.2 μm;

[0132] At the same time, graphene-modified aluminum alloy microspheres were prepared: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in comparative example 3 in Table 6, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene were placed in a smelting furnace at 700° C. After all the raw materials were completely melted, they were refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres were obtained by a spray method, with a particle size D 50 =13.7 microns.

[0133] The difference between Comparative Example 7 and Example 1 is that: Step 1, preparation of matrix aluminum alloy microspheres: According to the mass percentage of the elements of the matrix aluminum alloy microspheres in Comparative Preparation Example 4 in Table 3, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, and aluminum cerium alloys are placed in a smelting furnace at 700° C. After all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then matrix aluminum alloy microspheres are obtained by spraying, and the particle size D 50 =13.5 μm;

[0134] At the same time, graphene-modified aluminum alloy microspheres were prepared: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in comparative example 4 in Table 6, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene were placed in a smelting furnace at 700° C. After all the raw materials were completely melted, they were refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres were obtained by spraying, with a particle size D 50 =13.7 microns.

[0135] The difference between Comparative Example 8 and Example 1 is that: Step 1, preparation of matrix aluminum alloy microspheres: According to the mass percentage of the elements of the matrix aluminum alloy microspheres in Comparative Preparation Example 5 in Table 3, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, and aluminum cerium alloys are placed in a smelting furnace at 700° C. After all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then matrix aluminum alloy microspheres are obtained by spraying, and the particle size D 50 =13.6 μm;

[0136] At the same time, graphene-modified aluminum alloy microspheres were prepared: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in comparative example 5 in Table 6, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene were placed in a smelting furnace at 700° C. After all the raw materials were completely melted, they were refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres were obtained by a spray method, with a particle size D 50 =13.9 microns.

[0137] The difference between Comparative Example 9 and Example 1 is that: Step 1, preparation of matrix aluminum alloy microspheres: According to the mass percentage of the elements of the matrix aluminum alloy microspheres in Comparative Preparation Example 6 in Table 3, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, and aluminum cerium alloys are placed in a smelting furnace at 700° C. After all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then the matrix aluminum alloy microspheres are obtained by spraying, and the particle size D 50 =13.5 μm;

[0138] At the same time, graphene-modified aluminum alloy microspheres were prepared: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in comparative example 6 in Table 6, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene were placed in a smelting furnace at 700° C. After all the raw materials were completely melted, they were refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres were obtained by a spray method, with a particle size D 50 =13.8 microns.

[0139] The difference between Comparative Example 10 and Example 1 is that: Step 1, preparation of matrix aluminum alloy microspheres: electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, and aluminum cerium alloys are placed in a smelting furnace at 700° C. after all raw materials are completely melted, and then refined, degassed, and deslaged to obtain an aluminum alloy melt, and then matrix aluminum alloy microspheres are obtained by spraying, and the particle size D 50 =13.5 μm;

[0140] Step 2: Place the base aluminum alloy microspheres prepared in step 1 and the unmodified graphene in a double-helix conical mixer at a mass ratio of 99.75:25, introduce argon to replace the air, introduce argon at a temperature of 0°C, and mix at a speed of 800 rpm for 2 hours under argon protection to obtain a mixed alloy powder.

[0141] The difference between Comparative Example 11 and Example 1 is that: in step 1, preparation of graphene-modified aluminum alloy microspheres: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in Comparative Preparation Example 8 in Table 4, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene are placed in a smelting furnace at 700° C., and after all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres are obtained by spraying, and the particle size D 50 =13.8 microns.

[0142] The difference between Comparative Example 12 and Example 1 is that: in step 1, preparation of graphene-modified aluminum alloy microspheres: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in Comparative Preparation Example 9 in Table 4, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene are placed in a smelting furnace at 700° C., and after all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres are obtained by a spray method, and the particle size D 50 =13.7 microns.

[0143] The difference between Comparative Example 13 and Example 1 is that: in step 1, preparation of graphene-modified aluminum alloy microspheres: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in Comparative Preparation Example 10 in Table 4, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene are placed in a smelting furnace at 700° C., and after all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres are obtained by a spray method, and the particle size D 50 = 13.4 microns. In the actual wire drawing process, step 4 to step 7, the wire breakage scrap rate of the light alloy conductor wire increased significantly.

[0144] The difference between Comparative Example 14 and Example 1 is that: in step 1, preparation of graphene-modified aluminum alloy microspheres: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in Comparative Preparation Example 11 in Table 4, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene are placed in a smelting furnace at 700° C., and after all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres are obtained by spraying, and the particle size D 50=13.8μm.

[0145] The difference between Comparative Example 15 and Example 1 is that: in step 1, preparation of graphene-modified aluminum alloy microspheres: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in Comparative Preparation Example 12 in Table 4, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene are placed in a smelting furnace at 700° C., and after all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres are obtained by a spray method, and the particle size D 50 =13.9μm.

[0146] The difference between Comparative Example 16 and Example 1 is that: in step 1, preparation of graphene-modified aluminum alloy microspheres: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in Comparative Preparation Example 13 in Table 4, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene are placed in a smelting furnace at 700° C., and after all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres are obtained by a spray method, and the particle size D 50 = 13.5 microns. In the actual wire drawing process, step 4 to step 7, the wire breakage scrap rate of the light alloy conductor wire increased significantly.

[0147] The difference between Comparative Example 17 and Example 1 is that: in step 1, preparation of graphene-modified aluminum alloy microspheres: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in Comparative Preparation Example 14 in Table 4, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene are placed in a smelting furnace at 700° C., and after all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres are obtained by a spray method, and the particle size D 50 =13.8μm.

[0148] The difference between Comparative Example 18 and Example 1 is that: in step 1, preparation of graphene-modified aluminum alloy microspheres: according to the element mass percentage of the graphene-modified aluminum alloy microspheres in Comparative Preparation Example 15 in Table 4, electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene are placed in a smelting furnace at 700° C., and after all the raw materials are completely melted, they are refined, degassed, and deslaged to obtain an aluminum alloy melt, and then graphene-modified aluminum alloy microspheres are obtained by spraying, and the particle size D50 =13.6μm.

[0149] The difference between Comparative Example 19 and Example 1 is that: in step 2, the base aluminum alloy microspheres and graphene-modified aluminum alloy microspheres prepared in step 1 are placed in a double-helix conical mixer at a mass ratio of 11:1, and mixed at a speed of 800 rpm for 2 hours in an air atmosphere to obtain a mixed alloy powder.

[0150] The difference between Comparative Example 20 and Example 1 is that the forming temperature is 560°C, the forming pressure is: first pressurized to 560MPa at 20MPa / s, held for 300s, then reduced to 100MPa at 10MPa / s, held for 120s, and finally reduced to 0MPa at 20MPa / s, the forming speed is 0.5mm / s, cooled to room temperature, and the burrs are polished to obtain a semi-finished aluminum alloy bar. After cooling to room temperature, solution treatment is performed. The solution treatment parameters are as follows: keep warm at 560°C for 2h, water quench to room temperature, and then perform artificial aging treatment. The artificial aging treatment parameters are as follows: keep warm at 165°C for 0.5h to obtain an aluminum alloy bar with a diameter of 10mm.

[0151] Performance test: 1. Elongation at break, yield strength, and tensile strength are measured using HH11013YZUFY universal tensile testing machine in accordance with GB / T 228.1-2010. 2. Conductivity test method: measured in accordance with GB / T 351-2019 metal material resistivity measurement method. The test results are shown in Table 7.

[0152] Table 7: Test parameters of light aluminum alloy conductor wires in Examples 1-20 and Comparative Examples 1-18

[0153]

[0154]

[0155]

[0156] It can be seen from Examples 1-6 and Comparative Examples 1-3 and Table 7 that when the content of modified graphene in the graphene-modified aluminum alloy microspheres is 3.0wt%, the light alloy conductor prepared by mixing the matrix aluminum alloy microspheres and the graphene-modified aluminum alloy microspheres in a mass ratio of (11-16):1 has high conductivity and good strength and flexural resistance, and is economical, which facilitates industrial mass production and reduces the total production cost.

[0157] From Example 1, Examples 7-12 and Comparative Examples 4-9 and Table 7, it can be seen that 0.002% to 0.01% Sr, 0.001% to 0.01% Sc, and 0.001% to 0.01% Ce are added to the aluminum alloy matrix, that is, appropriate addition of Sr, Sc, and Ce can improve the conductivity, mechanical strength, and flexural resistance of the light alloy conductor to a certain extent, and improve the wire drawing processing performance.

[0158] It can be seen from Example 1, Examples 13-19 and Comparative Examples 10-18 and Table 7 that the content of modified graphene in the graphene-modified aluminum alloy microspheres is 3.0-6.0wt%, which can improve the conductivity, mechanical strength and flexural resistance of the light alloy conductor while ensuring the wire drawing performance of the light alloy conductor.

[0159] It can be seen from Example 1 and Comparative Example 19 and Table 7 that the preparation method of the mixed alloy powder provided in step 2 can improve the conductivity, mechanical strength, and flexural resistance of the light alloy conductor, and improve the wire drawing performance, that is, the introduction of low-temperature argon gas during the mixing process can reduce the generation of oxidative impurities.

[0160] It can be seen from Example 1 and Comparative Example 20 and Table 7 that the hot isostatic pressing treatment provided in step 3 can improve the electrical conductivity, mechanical strength and flexural resistance of the light alloy conductor.

[0161] In summary, the light alloy conductor wire for new energy vehicles prepared in the present invention has excellent electrical conductivity and good mechanical strength, flexural resistance, high toughness, and processing performance, and is easy to realize industrial mass production, thereby reducing the overall production cost of the light alloy conductor wire for new energy vehicles.

Claims

1. A process for preparing a light alloy conductor for new energy vehicles, characterized in that: The following steps are involved: Step 1, preparation of matrix aluminum alloy microspheres: according to the mass percentage of the elements of the matrix aluminum alloy microspheres, the mass percentage of the elements of the matrix aluminum alloy microspheres are as follows: 0.15% to 0.25% Mg, 0.15% to 0.25% Fe, 0.15% to 0.30% Cu, 0.10% to 0.20% Si, 0.003% to 0.005% Ti, 0.003% to 0.005% V, 0.05% to 0.15% Zr, 0.003% to 0.01% B, 0.002% ~0.01% Sr, 0.001%~0.01% Sc, 0.001%~0.01% Ce, the total content of inevitable impurities <0.15%, and the balance is aluminum; electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, and aluminum cerium alloys are placed in a smelting furnace at 690°C~710°C, and after all raw materials are completely melted, they are refined, degassed, and deslaged to obtain aluminum alloy melts, and then matrix aluminum alloy microspheres are obtained by a spray method; Preparation of graphene-modified aluminum alloy microspheres: According to the element mass percentage of the graphene-modified aluminum alloy microspheres, the mass percentage of the elements of the graphene-modified aluminum alloy microspheres are as follows: 3-6% modified graphene, 0.15%-0.25% Mg, 0.15%-0.25% Fe, 0.15%-0.30% Cu, 0.10%-0.20% Si, 0.003%-0.005% Ti, 0.003%-0.005% V, 0.05%-0.15% Zr, 0.003%-0.01% B: 0.0 0.02% to 0.01% Sr: 0.001% to 0.01% Sc, 0.001% to 0.01% Ce, the total content of inevitable impurities <0.15%, and the balance is aluminum; placing electrolytic aluminum ingots, magnesium ingots, aluminum silicon alloys, aluminum copper alloys, aluminum iron alloys, aluminum zirconium alloys, aluminum vanadium alloys, aluminum titanium alloys, aluminum boron alloys, aluminum strontium alloys, aluminum scandium alloys, aluminum scandium alloys, aluminum cerium alloys, and modified graphene in a smelting furnace at 690° C. to 710° C., refining, degassing, and deslagging to obtain an aluminum alloy melt after all raw materials are completely melted, and then preparing graphene-modified aluminum alloy microspheres by a spray method; The modified graphene is graphene modified with surface nano-aluminum clusters and / or graphene modified with single-atom aluminum; Step 2, placing the matrix aluminum alloy microspheres and graphene-modified aluminum alloy microspheres prepared in step 1 in a double-helix conical mixer at a mass ratio of (11-16):1 and mixing them evenly to obtain a mixed alloy powder; Step 3, placing the mixed alloy powder obtained in step 2 in a forming mold for hot isostatic pressing, cooling to room temperature, performing solution treatment and artificial aging treatment to obtain an aluminum alloy rod with a diameter of 8-12 mm; Step 4: Aluminum alloy bars with a diameter of 8-12 mm are subjected to primary wire drawing and primary intermediate annealing. The diameter of the aluminum alloy bars with a diameter of 8-12 mm is marked as Φ 初 The angle α of the extrusion die used in the primary wire drawing process is 15-30°, the primary intermediate annealing parameters are 360-385℃ for 80-160min, and the diameter of the aluminum alloy rod obtained by the primary wire drawing process and the primary intermediate annealing is Φ1, Φ1=0.3-0.6Φ 初 ; Step 5: The aluminum alloy bar with a diameter of Φ1 in step 4 is subjected to secondary wire drawing and secondary intermediate annealing. The angle α of the extrusion die used in the secondary wire drawing is 15-30°, and the secondary intermediate annealing parameters are 360-385°C for 80-160min. The diameter of the aluminum alloy bar obtained by the secondary wire drawing and the secondary intermediate annealing is Φ2, Φ2=0.15-0.30Φ 初 ; Step 6: The aluminum alloy bar with a diameter of Φ2 in step 5 is subjected to three-stage wire drawing and three-stage intermediate annealing. The angle α of the extrusion die used in the three-stage wire drawing is 15-30°, and the three-stage intermediate annealing parameters are 360-385°C for 80-160min. The diameter of the aluminum alloy bar obtained by the three-stage wire drawing and the three-stage intermediate annealing is Φ3, Φ3=0.08-0.15Φ 初 ; Step 7: The aluminum alloy bar with a diameter of Φ3 in step 6 is subjected to four-stage wire drawing and four-stage intermediate annealing. The angle α of the extrusion die used in the four-stage wire drawing is 15-30°, and the four-stage intermediate annealing parameters are 360-385°C for 80-160min. The diameter of the aluminum alloy bar obtained by the four-stage wire drawing and four-stage intermediate annealing is Φ4, Φ4=0.03-0.06Φ 初 ; Step eight, the aluminum alloy rod with a diameter of Φ4 in step seven is subjected to final annealing treatment to obtain a finished light alloy conductor, and the final annealing treatment parameters are as follows: continuous heat treatment at 480-540° C. for 0.40-0.50 s.

2. The process for preparing a light alloy conductor for new energy vehicles according to claim 1, characterized in that: The second step is to place the base aluminum alloy microspheres and graphene modified aluminum alloy microspheres prepared in the first step in a double-helix conical mixer at a mass ratio of (11-16):1, introduce argon gas to replace the air, introduce argon gas at a temperature of 0-5°C, and mix at a speed of 600-800 rpm for 2-4 hours under argon protection to obtain a mixed alloy powder.

3. The process for preparing a light alloy conductor for new energy vehicles according to claim 2, characterized in that: The hot isostatic pressing treatment parameters in step 3 are as follows: molding temperature 480-580°C, molding pressure: first pressurize to 200±20MPa at 20MPa / s, hold pressure for 30±5s, then pressurize to 300±20MPa at 10MPa / s, hold pressure for 30±5s, then pressurize to 400±20MPa at 5MPa / s, hold pressure for 30±5s, then pressurize to 460±20MPa at 1MPa / s, hold pressure for 60±5s, then pressurize to 560±20MPa at 0.5MPa / s, hold pressure for 100±5s, then reduce pressure to 300±20MPa at 1.0MPa / s, hold pressure for 60±5s, then reduce pressure to 200±20MPa at 5MPa / s, hold pressure for 60±5s, then reduce pressure to 100±20MPa at 10MPa / s MPa, maintain the pressure for 60±5s, and finally reduce the pressure to 0MPa at 20MPa / s. The forming speed is 0.2-2mm / s. After cooling to room temperature, the semi-finished aluminum alloy bar can be obtained by grinding the burrs.

4. The process for preparing a light alloy conductor for new energy vehicles according to claim 4 is characterized in that: The solution treatment parameters in step 3 are as follows: quenching at 540-560° C. for 1-4 hours.

5. The process for preparing a light alloy conductor for new energy vehicles according to claim 5, characterized in that: The artificial aging treatment parameters in step 3 are as follows: keeping warm at 150-180° C. for 0.1-4 h.

6. The process for preparing a light alloy conductor for new energy vehicles according to claim 1, characterized in that: The first-stage intermediate annealing parameters of step 4 are 360°C for 100-120 minutes, and the diameter of the aluminum alloy rod obtained by the first-stage wire drawing and the first-stage intermediate annealing is Φ1, Φ1=0.40Φ 初 .

7. The process for preparing a light alloy conductor for new energy vehicles according to claim 6, characterized in that: The secondary intermediate annealing parameters of step 5 are 370° C. for 100-120 min. The diameter of the aluminum alloy rod obtained by the secondary wire drawing and the secondary intermediate annealing is Φ2, Φ2=0.20Φ 初 .

8. The process for preparing a light alloy conductor for new energy vehicles according to claim 7, characterized in that: The parameters of the three-stage intermediate annealing in step 6 are 380° C. for 100-120 min. The diameter of the aluminum alloy rod obtained by the three-stage wire drawing and the three-stage intermediate annealing is Φ3, where Φ3=0.10Φ 初 .

9. The process for preparing a light alloy conductor for new energy vehicles according to claim 8, characterized in that: The parameters of the four-stage intermediate annealing in step seven are 385° C. for 100-120 min. The diameter of the aluminum alloy rod obtained by the four-stage wire drawing and the four-stage intermediate annealing is Φ4, where Φ4=0.03-0.06Φ 初 The diameter of the aluminum alloy bar Φ4 is customized according to actual needs.

10. The process for preparing a light alloy conductor for new energy vehicles according to claim 1, characterized in that: The surface nano-aluminum cluster loading rate in the graphene modified with the surface nano-aluminum clusters is 8-20wt%; the single-atom aluminum loading rate in the single-atom aluminum modified graphene is 5-10wt%.

Citation Information

Patent Citations

  • A high conductivity aluminum alloy rod and its preparation method

    CN110629076B

Cited By

  • Preparation process of ultrafine copper conductor for new energy automobile

    CN120280222A

  • Preparation process of ultra-fine copper conductor for new energy vehicles

    CN120280222B